Grand strategy in theory and practice the need for an effective American foreign policy - Martel, William C. 1955-2015 (Cambridge University Press, 2015)
"Grand Strategy in Theory and Practice The Need for an Effective American Foreign Policy This book explores fundamental questions about grand strategy, as it has evolved across generations and countries. It provides an overview of the Ancient Era of grand strategy and a detailed discussion of its philosophical, military, and economic foundations in the Modern Era. The author investigates these aspects through the lens of four approaches - those of historians, social scientists, practitioners, and military strategists. The main goal is to provide contemporary policymakers and scholars with an historic and analytic framework through which to evaluate and conduct grand strategy. By providing greater analytical clarity about grand strategy and describing its nature and utility for the state, the book presents a comprehensive theory and practice of grand strategy in order to articulate the United States' past, present and future purpose and position on the world stage"..